A DCRC Model for Text Classification - Hao, Zhaoquan; Jin, Jiangyong; Liang, Shengbin; Cheng, Suying; Shen, Yanqing (Computer and Information Science, 2023)
Traditional text classification models have some drawbacks, such as the inability of the model to focus on important parts of the text contextual information in text processing. To solve this problem, we fuse the long and short-term memory network BiGRU with a convolutional neural network to receive text sequence input to reduce the dimensionality of the input sequence and to reduce the loss of text features based on the length and context dependency of the input text sequence. Considering the extraction of important features of the text, we choose the long and short-term memory network BiLSTM to capture the main features of the text and thus reduce the loss of features. Finally, we propose a BiGRU-CNN-BiLSTM model (DCRC model) based on CNN, GRU and LSTM, which is trained and validated on the THUCNews and Toutiao News datasets. The model outperformed the traditional model in terms of accuracy, recall and F1 score after experimental comparison.
Keywords: BiGRU; BiLSTM; CNN; Text classification

A medical text classification approach with ZEN and capsule network - Liang, Shengbin; Sun, Fuqi; Sun, Haoran; Chen, Tingting; Du, Wencai (The Journal of Supercomputing, 2023)
Text classification is an important topic in natural language processing, with the development of social network, many question-and-answer pairs regarding health-care and medicine flood social platforms. It is of great social value to mine and classify medical text and provide targeted medical services for patients. The existing algorithms of text classification can deal with simple semantic text, especially in the field of Chinese medical text, the text structure is complex and includes a large number of medical nomenclature and professional terms, which are difficult for patients to understand. We propose a Chinese medical text classification model using a BERT-based Chinese text encoder by N-gram representations (ZEN) and capsule network, which represent feature uses the ZEN model and extract the features by capsule network, we also design a N-gram medical dictionary to enhance medical text representation and feature extraction. The experimental results show that the precision, recall and F1-score of our model are improved by 10.25%, 11.13% and 12.29%, respectively, compared with the baseline models in average, which proves that our model has better performance.
Keywords: Capsule network; Medical text classification; Text mining; ZEN model

A Model of Integrating Bert and BiGRU+ Attention Dual-channel Mechanism for Investor Sentiment Analysis of Stock Price Forecast - Ma, Huawei; Ma, Jixin; Liang, Shengbin; Du, Wencai (2022 IEEE/ACIS 23rd International Conference on Software Engineering, Artificial Intelligence, Networking and Parallel/Distributed Computing (SNPD), 2022)
Investor sentiment and emotions have a strong impact on financial markets. In recent years there has been increasing interest in analyzing the sentiment of investors for stock price prediction using machine learning. Existing prediction models mostly depend on the analysis of trading data and company profit. few prediction theories have been built based on individual investors' sentiments. The fundamental reason is the difficulty to measure individual investors' sentiment.
ISSN: 2693-8421

A model of integrating convolution and BiGRU dual-channel mechanism for Chinese medical text classifications - Li, Xiaoli; Zhang, Yuying; Jin, Jiangyong; Sun, Fuqi; Li, Na; Liang, Shengbin (PLOS ONE, 2023)
Recently, a lot of Chinese patients consult treatment plans through social networking platforms, but the Chinese medical text contains rich information, including a large number of medical nomenclatures and symptom descriptions. How to build an intelligence model to automatically classify the text information consulted by patients and recommend the correct department for patients is very important. In order to address the problem of insufficient feature extraction from Chinese medical text and low accuracy, this paper proposes a dual channel Chinese medical text classification model. The model extracts feature of Chinese medical text at different granularity, comprehensively and accurately obtains effective feature information, and finally recommends departments for patients according to text classification. One channel of the model focuses on medical nomenclatures, symptoms and other words related to hospital departments, gives different weights, calculates corresponding feature vectors with convolution kernels of different sizes, and then obtains local text representation. The other channel uses the BiGRU network and attention mechanism to obtain text representation, highlighting the important information of the whole sentence, that is, global text representation. Finally, the model uses full connection layer to combine the representation vectors of the two channels, and uses Softmax classifier for classification. The experimental results show that the accuracy, recall and F1-score of the model are improved by 10.65%, 8.94% and 11.62% respectively compared with the baseline models in average, which proves that our model has better performance and robustness.
Publisher: Public Library of Science
Keywords: Convolution; Deep learning; Machine learning; Memory recall; Neural networks; Recurrent neural networks; Semantics; Syntax

A Multi-Channel Text Sentiment Analysis Model Integrating Pre-training Mechanism - Liang, Shengbin; Jin, Jiangyong; Du, Wencai; Qu, Shenming (Information Technology and Control, 2023)
The number of tourist attractions reviews, travel notes and other texts has grown exponentially in the Internet age. Effectively mining users’ potential opinions and emotions on tourist attractions, and helping to provide users with better recommendation services, which is of great practical significance. This paper proposes a multi-channel neural network model called Pre-BiLSTM combined with a pre-training mechanism. The model uses a combination of coarse and fine- granularity strategies to extract the features of text information such as reviews and travel notes to improve the performance of text sentiment analysis. First, we construct three channels and use the improved BERT and skip-gram methods with negative sampling to vectorize the word-level and vocabulary-level text, respectively, so as to obtain more abundant textual information. Second, we use the pre-training mechanism of BERT to generate deep bidirectional language representation relationships. Third, the vectors of the three channels are input into the BiLSTM network in parallel to extract global and local features. Finally, the model fuses the text features of the three channels and classifies them using SoftMax classifier. Furthermore, numerical experiments are conducted to demonstrate that Pre-BiLSTM outperforms the baselines by 6.27%, 12.83% and 18.12% in average in terms of accuracy, precision and F1-score.
Number: 2
Keywords: Pre-training mechanism

An Improved Dual-Channel Deep Q-Network Model for Tourism Recommendation - Liang, Shengbin; Jin, Jiangyong; Ren, Jia; Du, Wencai; Qu, Shenming (Big Data, 2023)
Keywords: context-aware; deep reinforcement learning; dual-channel; tourism recommendation

Hierarchical Medical Classification Based on DLCF - Yao, Mingyuan; Sun, Haoran; Liang, Shengbin; Shen, Yanqing; Yukie, Niki (Computer and Information Science, 2023)
Medical classification is affected by many factors, and the traditional medical classification is usually restricted by factors such as too long text, numerous categories and so on. In order to solve these problems, this paper uses word vector and word vector to mine the text deeply, considering the problem of scattered key features of medical text, introducing long-term and short-term memory network to effectively retain the features of historical information in long text sequence, and using the structure of CNN to extract local features of text, through attention mechanism to obtain key features, considering the problems of many diseases, by using hierarchical classification. To stratify the disease. Combined with the above ideas, a deep DLCF model suitable for long text and multi-classification is designed. This model has obvious advantages in CMDD and other datasets. Compared with the baseline models, this model is superior to the baseline model in accuracy, recall and other indicators.
Keywords: Dual channel; Hierarchical classification; LSTM-CNN; Medical classification; RF

Java面向对象程序设计 - 梁胜彬 (清华大学出版社, 2023)
结合实用案例讲解Java语法、面向对象程序设计技术和核心API。 全书共10章，内容涵盖Java概述、Java语法基础、面向对象基础、面向对象高级技术、 Java API、异常处理机制、Java I/O流、多线程、Java GUI编程和Java网络编程等知识要点。案例丰富，以JDK 17和IntelliJ IDEA等流行的开发环境为依托，力求让读者通过案例 掌握Java编程技术。另一个特色是在阐释专业内容的同时自然融入思政元素， 具有鲜明的时代性和引领性。 可作为普通高等院校计算机、软件工程、人工智能等专业“面向对象程序设计”“Java程序设计”课程的教材，也适 合编程爱好者自学和培训使用。

LSDA-APF: A Local Obstacle Avoidance Algorithm for Unmanned Surface Vehicles Based on 5G Communication Environment - Li, Xiaoli; Jiao, Tongtong; Ma, Jinfeng; Duan, Dongxing; Liang, Shengbin (Computer Modeling in Engineering & Sciences, 2023)
In view of the complex marine environment of navigation, especially in the case of multiple static and dynamic obstacles, the traditional obstacle avoidance algorithms applied to unmanned surface vehicles (USV) are prone to fall into the trap of local optimization. Therefore, this paper proposes an improved artificial potential field (APF) algorithm, which uses 5G communication technology to communicate between the USV and the control center. The algorithm introduces the USV discrimination mechanism to avoid the USV falling into local optimization when the USV encounter different obstacles in different scenarios. Considering the various scenarios between the USV and other dynamic obstacles such as vessels in the process of performing tasks, the algorithm introduces the concept of dynamic artificial potential field. For the multiple obstacles encountered in the process of USV sailing, based on the International Regulations for Preventing Collisions at Sea (COLREGS), the USV determines whether the next step will fall into local optimization through the discrimination mechanism. The local potential field of the USV will dynamically adjust, and the reverse virtual gravitational potential field will be added to prevent it from falling into the local optimization and avoid collisions. The objective function and cost function are designed at the same time, so that the USV can smoothly switch between the global path and the local obstacle avoidance. The simulation results show that the improved APF algorithm proposed in this paper can successfully avoid various obstacles in the complex marine environment, and take navigation time and economic cost into account.
Publisher: Tech Science Press